Should the world collaborate imminently to develop neglected live‐attenuated vaccines for COVID‐19? - Chen, Ji‐Ming (Journal of medical virology, 2022)
The rapid spread of the Delta variant suggests that SARS‐CoV‐2 will likely be rampant for months or years and could claim millions of more lives. All the known vaccines cannot well defeat SARS‐CoV‐2 due to their limited efficacy and production efficiency, except for the neglected live‐attenuated vaccines (LAVs), which could have a much higher efficacy and much higher production efficiency than other vaccines. LAVs, like messiahs, have defeated far more pathogenic viruses than other vaccines in history, and most current human vaccines for viral diseases are safe LAVs. LAVs can block completely infection and transmission of relevant viruses and their variants. They can hence inhibit the emergence of vaccine‐escape and virulence‐enhancing variants and protect immunologically abnormal individuals better in general. The safety of COVID‐19 LAVs, which could save millions of more lives, can be solidly guaranteed through animal experiments and clinical trials. The safety of COVID‐19 LAVs could be greatly enhanced with intramuscular or oral administration, or administration along with humanized neutralizing monoclonal antibodies. Together, extensive global collaboration, which can greatly accelerate the development of safe COVID‐19 LAVs, is imminently needed.